Education Level and Work Period as Determinants of Personal Protective Equipment Compliance Among Nurses at Makassar Regional General Hospital - Rahmilah, Mitha; Ulfiana Fitri, Andi; Kadek Risnayanti (Journal of Scientific Insights, 2026)
Nurses’ compliance with occupational safety procedures is an important factor in maintaining the quality of healthcare services and preventing the risk of accidents and infections in hospitals. Education level and length of service are individual factors that are assumed to influence the level of compliance. This study aimed to analyze the relationship between nurses’ education level and length of service and their compliance with occupational safety procedures in hospitals. This study employed a quantitative design with a cross-sectional approach. The population consisted of all nurses working in the hospital, and the sampling technique used was total sampling. Data were collected using questionnaires and observation sheets, and then analyzed using the chi-square test and Fisher’s Exact Test with a significance level of 0.05. The results showed that there was a significant relationship between education level and nurses’ compliance (p < 0.05). In addition, length of service was also significantly associated with nurses’ compliance (p < 0.05). Nurses with higher education levels and longer work experience tended to have better compliance levels. In conclusion, education level and length of service are significantly associated with nurses’ compliance in implementing occupational safety procedures. Therefore, hospitals need to improve continuous training and supervision for nurses to enhance compliance with occupational safety standards.